2009
DOI: 10.1289/ehp.0800281
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine Exposure and Incidence of Diabetes in a Cohort of Great Lakes Sport Fish Consumers

Abstract: BackgroundStudies have demonstrated ubiquitous human exposure to persistent organic pollutants (POPs) such as p,p′-diphenyldichloroethene (DDE) and polychlorinated biphenyls (PCBs). Although there is considerable evidence that POP exposures are associated with prevalent diabetes, these studies do not establish causality because the cross-sectional study design does not allow for assessment of temporality of the exposure–disease association. Prospective studies, however, have been lacking.ObjectivesThis study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
130
5
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(148 citation statements)
references
References 35 publications
(76 reference statements)
9
130
5
3
Order By: Relevance
“…Retrospective epidemiological analysis showed that increased levels of DDE in the human sera were positively correlated with increased insulin resistance (Lee et al, 2007) and prevalence of T2D (Lee et al, 2006). In addition, studies of a Swedish cohort (Rignell-Hydbom et al, 2007), the Great Lake fish consumers (Turyk et al, 2009), as well as recent analysis of 72 epidemiological studies (Taylor et al, 2013) and meta-analysis of 23 epidemiological studies (Tang et al, 2014), found a strong association between DDE exposure and increased incidence of T2D. However, it should be noted that these data were insufficient to establish causality.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective epidemiological analysis showed that increased levels of DDE in the human sera were positively correlated with increased insulin resistance (Lee et al, 2007) and prevalence of T2D (Lee et al, 2006). In addition, studies of a Swedish cohort (Rignell-Hydbom et al, 2007), the Great Lake fish consumers (Turyk et al, 2009), as well as recent analysis of 72 epidemiological studies (Taylor et al, 2013) and meta-analysis of 23 epidemiological studies (Tang et al, 2014), found a strong association between DDE exposure and increased incidence of T2D. However, it should be noted that these data were insufficient to establish causality.…”
Section: Discussionmentioning
confidence: 99%
“…The associations between the serum concentrations of organochlorine pesticides and the prevalence of diabetes were examined in the Mexican-American population (Cox et al, 2007) and Korean population (Son et al, 2010). Exposure of p,p'-DDE was related to the incidence of diabetes in a cohort of Great Lakes sport fish consumers from 1994 to 2005 (Turyk et al, 2009). Lee et al (2010) also investigated whether several persistent organic pollutants predict the risk of type 2 diabetes within the Coronary Artery Risk D e v e l o p m e n t i n Y o u n g A d u l t s ( C A R D I A ) c o h o r t ( L e e e t a l .…”
Section: Diabetesmentioning
confidence: 99%
“…Consequently, it is not unlikely that POPs, which mainly accumulate in fat tissues, contribute to the production and release of inflammation-related adipose tissue proteins known to be involved in the development of chronic metabolic disorders such as T2DM. A number of studies have found associations between T2DM and POPs, such as polychlorinated biphenyls, [74][75][76][77][78] polychlorinated dibenzo-p-dioxins [75][76][77]79 and organochlorine pesticides, [74][75]77,[80][81][82] which are usually detectable at low levels in humans. The previous observations arise from crosssectional studies, making it difficult to establish a causeeffect relationship.…”
Section: Risksmentioning
confidence: 99%
“…[81][82][83] Among women from the general Swedish population, RignellHydbom et al 83 showed that women with the highest exposed quartile for p,p 0 -dichlorodiphenyldichloroethane had a fivefold increased risk of developing T2DM compared with their controls, 6 years after the baseline examination. Furthermore, using the cohort of the Great Lakes sport fish consumers, Turyk et al 81,82 showed that plasma concentrations of p,p 0 -dichlorodiphenyldichloroethane and the sum of polychlorinated biphenyls were higher in participants who subsequently developed diabetes. Even though direct experimental evidence linking POPs with the prevalence of obesity and T2DM has not yet been demonstrated, this association raises public health concerns, particularly in northern aboriginal communities that are likely more exposed to these substances owing to their geographical location and traditional dietary habits.…”
Section: Risksmentioning
confidence: 99%